Contemporary Arabic Vocabulary Acquisition in Pesantren: Challenges and Pedagogical Innovations - Achmad Makki Lazuardi (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
This study examines the effectiveness of role-playing techniques in enhancing Arabic speaking proficiency among female learners in an Islamic boarding school. The research aims to evaluate how role-playing activities influence learners’ fluency, vocabulary use, pronunciation accuracy, and communicative confidence. Adopting a mixed-methods design, the study integrates quantitative pre- and post-test measurements with qualitative classroom observations and semi-structured interviews. Quantitative analysis reveals a statistically significant improvement in students’ overall speaking performance (p < 0.001), with the most notable gains observed in fluency and self-rated speaking confidence. Qualitative findings further indicate that role-playing activities reduce speaking anxiety, increase learner motivation, and foster higher levels of classroom engagement by providing meaningful and contextually relevant communicative practice. Grounded in Communicative Language Teaching (CLT) and Vygotsky’s sociocultural theory, the findings suggest that interactive and gender-sensitive pedagogical approaches create a supportive learning environment that facilitates authentic language use. The study concludes that role-playing serves not only as a speaking practice technique but also as an affective scaffold that empowers female learners to participate more actively in Arabic communication. Practically, the study offers an adaptable instructional model for Arabic educators seeking to integrate experiential learning strategies to bridge linguistic competence and communicative confidence in speaking instruction.